1995
DOI: 10.1016/0014-5793(94)01301-g
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases‐2 (TIMP‐2) in rat liver cells is increased by lipopolysaccharide and prostaglandin E2

Abstract: To explore the functional role of TIMP-2 in liver, we determined TIMP-2 mRNA levels in primary rat hepatocytes and in total rat liver. Rat hepatocytes constitutively express TIMP-2 mRNA at a low level. Incubation with dexamethasone, prostaglandin E2 and a combination of inflammatory cytokines leads to an up-regulation of TIMP-2 mRNA. In rats in vivo we found a dramatic increase of TIMP-2 expression after intraperitoneal injection of lipopolysaccharide. Compared to our previous findings on TIMP-1 we conclude th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 37 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Without any sign of fibrosis TIMP-2 elevation was presumably inflammation-or virus-related. In animal models of acute toxic liver injury rat TIMP-2 mRNA peaked transiently 2-3 days after a single injection of CCl 4 [48] or LPS [60]. Consistently, in chronic toxic liver injury no significant increase was observed in rats during an 8-week CCl 4 -challenge [29].…”
Section: Mmps and Timps In Fibrogenesismentioning
confidence: 58%
See 1 more Smart Citation
“…Without any sign of fibrosis TIMP-2 elevation was presumably inflammation-or virus-related. In animal models of acute toxic liver injury rat TIMP-2 mRNA peaked transiently 2-3 days after a single injection of CCl 4 [48] or LPS [60]. Consistently, in chronic toxic liver injury no significant increase was observed in rats during an 8-week CCl 4 -challenge [29].…”
Section: Mmps and Timps In Fibrogenesismentioning
confidence: 58%
“…Initial evidence regarding the relatedness of TIMP-1 and TIMP-2, and hepatic fibrosis relies on findings in rat hepatocytes: in this setting treatment with inflammatory cytokines stimulated the transcription of both genes [58][59][60]. Later, enhanced expression of TIMP-1 and TIMP-2 was shown in two rat models of liver injury, provoked via CCl 4 injection and bile duct ligation [61].…”
Section: Mmps and Timps In Fibrogenesismentioning
confidence: 96%
“…In ovine trophoblast, Cox-2 expression and the associated prostaglandin production could be the way in which the cells control the invasion of the trophoblast. It was effectively reported that cyclooxygenase end-products suppressed the production of metalloproteinases [52,53] and enhanced the expression of their inhibitors [54][55][56]. However, in other models, prostaglandins were also found to promote the synthesis of proteolytic enzymes [57][58][59].…”
Section: Discussionmentioning
confidence: 98%
“…PGE2 plays an important role in liver pathogenesis. For example, PGE2 delays collagen formation and up-regulates tissue inhibitor of metalloproteinases-2 leading to matrix accumulation in rat liver [21]. It has been shown that plasma levels of PGE2 increase with the advancement of liver cirrhosis [22].…”
Section: Discussionmentioning
confidence: 99%